The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.5380/rf.v42i4.26952
|View full text |Cite
|
Sign up to set email alerts
|

AVALIAÇÃO TÉCNICA E DE CUSTOS DE PODA MANUAL E SEMIMECANIZADA EM PLANTIOS DE Pinus taeda

Abstract: ResumoO objetivo desta pesquisa foi realizar uma avaliação técnica e de custos das atividades de poda manual e semimecanizada em plantios de Pinus taeda L., visando gerar informações para o aumento da produtividade, melhoria da qualidade e redução dos custos de produção. A pesquisa foi conduzida em uma empresa prestadora de serviços florestais, localizada na região do Norte Pioneiro, Estado do Paraná. Foram estudadas as atividades de podas executadas a 2,5 m; 4,0 m e 5,0 m de altura. A avaliação técnica consis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 1 publication
0
2
0
3
Order By: Relevance
“…A machadinha aferiu 32% dos cortes irregulares, com presença de fragmentos de galhos. A motopoda possibilitou o corte rente ao fuste, até os galhos que se encontravam entrelaçados, resultado similar ao encontrado por Oliveira et al (2012) na poda de pinus.…”
Section: Resultsunclassified
See 2 more Smart Citations
“…A machadinha aferiu 32% dos cortes irregulares, com presença de fragmentos de galhos. A motopoda possibilitou o corte rente ao fuste, até os galhos que se encontravam entrelaçados, resultado similar ao encontrado por Oliveira et al (2012) na poda de pinus.…”
Section: Resultsunclassified
“…Os custos operacionais da motopoda foram semelhantes aos encontrados por Oliveira et al (2012) na avaliação da atividade de poda de pinus. Entretanto, os autores encontraram maiores custos de produção para a motopoda em comparação ao sistema manual.…”
Section: Resultsunclassified
See 1 more Smart Citation
“…Regarding the quality of manual and mechanized mowing, although no statistical difference was found by means of the nonparametric test, it was observed that the number of trees with injuries was lower in the manual mowing area. As observed by Oliveira et al (2012), when evaluating the quality of semi-mechanized pruning in stands of Pinus taeda, it is possible to relate the level of training and orientation of the crews with the occurrence of injuries. Thus, the greater the ability of team members who perform manual mowing, the lower the average percentage of injuries per hectare.…”
Section: Discussionmentioning
confidence: 99%
“…The pruning management reduces and concentrates the incidence of knots in the wood and, therefore, results in higher added-value products (Oliveira et al, 2020). Pruning management is relevant, especially in the plantations where the species do not have natural pruning (Oliveira et al, 2012).…”
Section: Introduction and Objectivesmentioning
confidence: 99%